PENGARUH PENGGUNAAN VIDEO PEMBELAJARAN DAN MINAT BELAJAR TERHADAP HASIL BELAJAR MATA KULIAH PENGANTAR MANAJEMEN PADA PROSES PEMBELAJARAN JARAK JAUH DI MASA PANDEMI COVID 19. - Sahara, Siti; Priyanto, Sugeng (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Currently, Covid-19 is a hot topic of conversation in all countries, including Indonesia. In Indonesia itself, a Large-Scale Social Restriction (PSBB) policy was implemented to suppress the spread of this virus so that all activities carried out outside the home must be stopped until this pandemic has subsided. The imposition of Large-Scale Social Restrictions (PSBB) made the learning system change from a classical system to a Distance Learning (PJJ) or online system. In the Introduction to Management course, student participation was found to be low during the learning process. Lecturers have difficulty determining whether students take learning seriously or not. Often in distance learning, some students deliberately put up a video that has been recorded, so that it seems like they are following the learning process, but in reality, they are doing something else. This is caused by several factors, including media which can be in the form of video lessons and student interest in learning. Looking at the description above, researchers are interested in conducting research that aims to determine the effect of using video learning and learning interest on learning outcomes in the Management Introduction course in the distance learning process during the Covid 19 pandemic. This research was conducted in the D3 Transportation Study Program, Faculty of Engineering, the State University of Jakarta in semester 113 of the 2020/2021 school year. This research is an ex post facto research with a quantitative approach. The number of samples in this study consisted of 76 students. The data collection technique is done by using questionnaires and documentation. The data obtained were analyzed using a multiple regression test. The results of this study indicate that Fcount ≥ Ftable = 13.53 ≥ 3.124 so it can be concluded that there is a significant influence between the use of instructional videos (X1) and interest (X2) on learning outcomes in the Introduction to Management (Y) course. For this reason, the role of lecturers is indispensable in continuously making creative innovations in developing various kinds of learning media that can increase student interest in learning during the Covid 19 pandemic.